Passivity/sliding mode control of a stand alone hybrid generation system - Valenciaga, Fernando (2000)
A novel variable structure controller for an electric generation hybrid system is proposed. The system is intended for variable alternate load and includes a wind turbine, photovoltaic generation and a battery bank. As a first step for the controller design, a dynamic model of the system is developed in a rotor reference frame. The control law is designed through the combination of passivity and sliding mode techniques. The objective is to control the operation of the wind subsystem to complement the photovoltaic generation, so the power demand is satisfied. During periods of scarce winds, the strategy is modified and the control objective becomes maximum wind generation.